Multi-criteria analysis of the environmental vulnerability of the cotton zone of Mali: Case of the northeast subsidiary of Koutiala - Barry, Tahirou; Diawara, Hamidou; Traoré, Souleymane Sidi; Attoubounou, Rachid Abdourahamane (International Journal of Environment, Agriculture and Biotechnology, 2024)
The northeast subsidiary of Koutiala is a very ancient and important cotton production zone in Mali. Commonly called old cotton basin of Mali, this subsidiary counting ten sectors divided between two divisions, is today finds confronted to environmental problems. However, it is difficult to locate the essential reasons of this problem so much the factors are numerous. To assess the impact of different factors on environment, this study devoted itself as objective to analyze the spatiotemporal dynamics of the environmental vulnerability of the northeast subsidiary of Koutiala between 2003 and 2017. It used several types of data for this purpose (climatic, satellite, socioeconomic and demographic, geographical). The used methodology was based on the Principal Component Analysis (PCA) and the Agglomerative Hierarchical Clustering (AHC), after standardizing the data using the empirical normalization method. The study reveals that the main factors of environmental vulnerability are mainly composed of indicators of occupation of the soil (NDVI and Occupancy rate of the soil by cultures which are present in 100.0% of the factors), socioeconomic (in 83.3%), climatic (in 66.7%) and socio-demographic (in 58.3%). It also reveals that the sector of Konséguéla in the southwest (division of Koutiala) is the least vulnerable contrary to that from Kimparana to the north (division of San) which is the most vulnerable. Globally between 2003 and 2017, there is a downward trend of the environmental vulnerability of the northeast subsidiary of Koutiala.